Climate variation influences host specificity in avian malaria parasites. (13th January 2019) - Fecchio, Alan; Wells, Konstans; Bell, Jeffrey A.; Tkach, Vasyl V.; Lutz, Holly L.; Weckstein, Jason D.; Clegg, Sonya M.; Clark, Nicholas J.
Abstract: Parasites with low host specificity (e.g. infecting a large diversity of host species) are of special interest in disease ecology, as they are likely more capable of circumventing ecological or evolutionary barriers to infect new hosts than are specialist parasites. Yet for many parasites, host specificity is not fixed and can vary in response to environmental conditions. Using data on host associations for avian malaria parasites (Apicomplexa: Haemosporida), we develop a hierarchical model that quantifies this environmental dependency by partitioning host specificity variation into region‐ and parasite‐level effects. Parasites were generally phylogenetic host specialists, infecting phylogenetically clustered subsets of available avian hosts. However, the magnitude of this specialisation varied biogeographically, with parasites exhibiting higher host specificity in regions with more pronounced rainfall seasonality and wetter dry seasons. Recognising the environmental dependency of parasite specialisation can provide useful leverage for improving predictions of infection risk in response to global climate change.